High-on-Aspirin Residual Platelet Reactivity Evaluated Using the Multiplate® Point-of-Care Device - Mărginean Alina (Acta Medica Marisiensis, 2016)
Objective: The aim of this study was to evaluate the prevalence of aspirin non-responsiveness using whole blood multiple electrode aggregometry and to investigate the role of different clinical and laboratory variables associated with the lack of response. Methods: The present study included 116 aspirin treated patients presented with acute coronary syndromes or stroke. Response to aspirin was assessed by impedance aggregometry using arachidonic acid as agonist, in a final concentration of 0.5 mM (ASPI test). Results: In our data set 81% (n=94) were responders and 19% (n=22) non-responders showing high-on-aspirin platelet reactivity. Correlation analysis showed that the ward of admittance, low-density lipoproteins (LDL), concomitant antibiotic treatment, beta-adrenergic receptor blockers, history of myocardial infarction as well as PCI performed on Cardiology patients have different degrees of association with aspirin response. Conclusion: Concomitant treatment with beta-adrenergic receptor inhibitors, history of myocardial infarction and Cardiology ward admittance significantly increased the chance of responding to aspirin treatment whereas antibiotic therapy and low-density lipoproteins cholesterol seemed to increase the risk of high-on-aspirin residual platelet reactivity.